STRATEGI MANAJER KAMPANYE BAGI KOMUNIKATOR POLITIK - Chontina Siahaan (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractIn the political life, a political communicator has a central role when he or she want to get aposition in the parliament either as president or vice president in the legislative, executiveor judicative branch. A strategic planning of the Campaign Manager is very important tobring a Political Communicator to be president. What has to be done by a campaignmanager and what kind of strategy will be used to achieve its goal will be described in thisarticle by mapping steps conducted by the Campaign Manager that using PEST andSWOT analysis and followed by campaign planning to answer five basic questions: whatwill be achieved, who is the target, what message will be conveyed, how to convey, how toevaluate and time and fund of its implementation.Keywords: Political communicator, Campaign manager, Strategic planning